De strijd der faculteiten: Een kantiaans perspectief op de wijsgerige godsleer, de theologie, de godsdienstfilosofie en de religiewetenschap - Loose, Donald (Tijdschrift voor theologie, 2008)
This article has two objectives that are to be seen against the background of Kant’s Conflict of the Faculties, a document in which Kant defended his Religion within the Boundaries of Mere Reason as a strictly philosophical study and in which he explained theologians’ and philosophers’ distinct approaches to religion. It first outlines Kant’s view of religion’s specificity alongside a philosophical doctrine of God or theology. Contrary to what is usually asserted, religion for Kant is not simply subsumed in an identification with ethics. In addition, this article envisages using concepts borrowed from Kant to clarify the demarcation between disciplines and to coordinate the various disciplines in academic research on religion. The author believes that a strict division is as impossible as it is undesirable. This applies as much to the relationship between theology and philosophy as it does to that of both of these to religious studies.